STEREOTIP DALAM KOMUNIKASI ANTAR BUDAYA PADA PAGUYUBAN MINORITAS MINANG DI UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA - Syintia Maharani, (2021)
Stereotypes are commonplace to be used as objects of joking or joking in the community. The research entitled "Stereotypes in Intercultural Communication in the Minang Minority Association at the Veterans National Development University, Jakarta", has a problem formulation to find out what stereotypes are accepted by Minangkabau students in the UPNVJ campus environment and how Minang students understand stereotypes so that there is no conflict between them. culture in the UPNVJ campus environment. The purpose of this study was to determine the impact of developing stereotypes on intercultural communication of members of the Minang ethnic community in the campus social environment. This study uses a phenomenological qualitative research method. The sources of data used are from in-depth interviews with selected Paguyuban members and two lecturers of communication science as key informants to strengthen research data. The theoretical basis used is Anxiety/ Uncertainty Management theory. The results of this study are that existing negative stereotypes should not be allowed to develop and it is necessary to increase knowledge that Indonesia is a diverse culture and society so that tolerance needs to be upheld so that there is no misunderstanding between people of different cultures.